Reconstructing Legal Frameworks for Post-Mining Reclamation Guarantees and Ecological Justice - Angga Kurniawan; Abdul Madjid; Istislam Istislam (Jurnal Ius Constituendum, 2025)
This study analyzes the effectiveness of post-mining reclamation guarantee fund regulations in achieving environmental restoration and reconstructs a normative framework oriented toward ecological justice. The current reduction of reclamation guarantees to mere administrative requirements demonstrates the failure of the law to provide substantive protection for citizens’ constitutional rights to a healthy environment. Using normative juridical research with legislative, conceptual, and historical approaches, this study employs prescriptive–analytical methods to evaluate the gap between legal norms and practice and to formulate a responsive legal model. The findings reveal that reclamation guarantee funds have not effectively functioned as substantive legal instruments due to regulatory disharmony between the Minerba Law and the Environmental Protection and Management Law (UUPPLH), weak supervision, and the absence of strict sanctions. The study proposes a reconstruction of the legal framework through harmonization of environmental and mining regulations, adoption of the polluter pays and strict liability principles, and strengthening of interagency coordination. In addition, the establishment of a transparent and participatory Multi-Stakeholder Monitoring Board and a public e-monitoring system is recommended to ensure accountability and ecological restoration. The novelty of this research lies in integrating constitutional and environmental justice perspectives into a double-track sanction system that combines preventive and repressive functions of reclamation guarantees. This approach advances the eco-constitutional paradigm by linking legal certainty, environmental accountability, and participatory governance in post-mining management.